Analysis of the Quality of Postpartum Care for Postpartum Mothers with Complications in Hospitals - Maidina Putri; Cakrawati R Cakrawati R (International Journal of Health Sciences, 2026)
ABSTRACTPostpartum care is a crucial component of maternal health services, ensuring the mother's recovery after delivery. For postpartum mothers with complications, the quality of postpartum care is crucial for preventing morbidity and mortality. This study aimed to analyze the quality of postpartum care for postpartum mothers with complications in the hospital. This study used a quantitative design with a cross-sectional approach. A sample of 90 respondents was selected using a purposive sampling technique. Data were collected through questionnaires and observations, then analyzed using the chi-square test and logistic regression. The results showed that the quality of postpartum care was influenced by the competence of health workers, the availability of facilities, and therapeutic communication (p < 0.05). The dominant factor was health worker competence (OR = 3.1). In conclusion, improving the quality of postpartum care requires a comprehensive approach that includes improving health worker competence and service quality.Keywords: Postpartum Care, Postpartum, Complications, Service Quality